Strong magnetic exchange and frustrated ferrimagnetic order in a weberite-type inorganic–organic hybrid fluoride. (27th May 2019) - Clark, L.; Albino, M.; Pimenta, V.; Lhoste, J.; da Silva, I.; Payen, C.; Grenèche, J.-M.; Maisonneuve, V.; Lightfoot, P.; Leblanc, M.
Abstract : We combine powder neutron diffraction, magnetometry and 57 Fe Mössbauer spectrometry to determine the nuclear and magnetic structures of a strongly interacting weberite-type inorganic–organic hybrid fluoride, Fe2 F5 (H taz ). In this structure, Fe 2+ and Fe 3+ cations form magnetically frustrated hexagonal tungsten bronze layers of corner-sharing octahedra. Our powder neutron diffraction data reveal that, unlike its purely inorganic fluoride weberite counterparts which adopt a centrosymmetric Imma structure, the room-temperature nuclear structure of Fe2 F5 (H taz ) is best described by a non-centrosymmetric Ima 2 model with refined lattice parameters a  = 9.1467(2) Å, b  = 9.4641(2) Å and c  = 7.4829(2) Å. Magnetic susceptibility and magnetization measurements reveal that strong antiferromagnetic exchange interactions prevail in Fe2 F5 (H taz ) leading to a magnetic ordering transition at T N  = 93 K. Analysis of low-temperature powder neutron diffraction data indicates that below T N, the Fe 2+ sublattice is ferromagnetic, with a moment of 4.1(1) µB per Fe 2+ at 2 K, but that an antiferromagnetic component of 0.6(3) µB cants the main ferromagnetic component of Fe 3+, which aligns antiferromagnetically to the Fe 2+ sublattice. The zero-field and in-field Mössbauer spectra give clear evidence of an excess of high-spin Fe 3+ species within the structure and a non-collinear magnetic structure. This article is part of the theme issue 'Mineralomimesis: natural and synthetic frameworks in science and technology'.